Value-Based Research in the Heritage Area of Chetinadu Region, Tamilnadu, India - RajivKumar, Seetha; Kesavaperumal, Thirumaran (Research Aspects in Arts and Social Studies Vol. 9, 2023)
The focus towards built heritage conservation is becoming increasingly popular in the current scenario. Every heritage building has its values or heritage significance, and its values are perceived differently by various stakeholders. The objective of this research is to identify and comprehend the values represented in the built heritage of the Chettinadu region. Chettinadu, a region in southern India, is located in the state of Tamil Nadu, 32 kilometers from the west coast of the Bay of Bengal, with a total area of 1,550 square kilometers in the heart of Tamil Nadu. Chettinadu's built heritage is an irreplaceable cultural resource that gives the state its unique identity and character. The Chettinadu region has been classified into three clusters in the UNESCO 2014 tentative list based on their Outstanding Universal Values, which serves as a framework for our research. In this paper, we investigated the historical context of heritage areas and buildings in the Chettinadu region and attempted to identify values in built heritage using a specified set of variables. To accomplish this goal, various parameters were examined to determine how the values of built heritage contribute to the unique sociocultural flavor of Chettinadu. Social, cultural, historical, and architectural values all contribute to the town's image, but determining their relative importance for conservation purposes is difficult, the analysis contributes to the evolution of strategies aimed at preserving and enhancing the region's built heritage. The varied heritage potential based on values will assist planners and developers in developing sustainable programs for protecting the inherent values of Chettinadu's built heritage.